Analisis usahatani tumpang sari tani kopi arabika Di desa babadan, kecamatan dukun, kabupaten magelang - pantja siwi v r ingesti (JURNAL VIGOR, 2025)
Arabica coffee (Coffea arabica) is a popular commodity with high economic value in the global market, especially in Indonesia. This study was conducted in Babadan Village, Dukun District, Magelang Regency, to analyze the income of Arabica coffee farmers who implement an intercropping system with tobacco and horticulture. A quantitative descriptive method was used to collect data from 30 farmers through questionnaires and interviews. The analysis included fixed and variable costs, farm income, and farm feasibility (R/C ratio). The results showed that: The average production and productivity of Arabica coffee intercropped with horticulture was higher than that of tobacco intercropping, with the highest income reaching IDR 69,836,411 per year for horticulture. The highest R/C ratio was also found for horticulture intercropping (2.63), indicating the feasibility of this farming activity. The study recommends developing financial management and agricultural technology to improve the sustainability of coffee farming in this location.